Biomechanical validation of novel Nuss procedure simulations for patients with various morphological types of pectus excavatum - Lim, Beop-Yong; I, Hoseok; Lee, Chiseung (Frontiers in Bioengineering and Biotechnology, 2023)
A novel Nuss procedure simulation was developed for patients with pectus excavatum considering the displacement of a metal bar and a chest wall model, including the intercostal muscles. However, this simulation was developed for a typical symmetrical patient among the various morphological types of pectus excavatum. Accordingly, this study aimed to validate and confirm the novel simulation for patients with eccentric and imbalanced types, which are severe types of pectus excavatum, considering factors such as depression depth and eccentricity among others. Three-dimensional models of chest walls and metal bars were created for three different types of patients. The rotation-equilibrium displacement and chest wall with intercostal muscles were set according to the methods and conditions of the novel Nuss procedure simulation. The anterior sternal translation and the Haller index derived from the simulation results were compared and verified using medical data from actual postoperative patients. Additionally, maximum equivalent stresses and strains were derived to confirm the suitability of the novel Nuss procedure for each patient type. The severe types had similar precision to the typical type when compared to the actual postoperative patient. Relatively high maximum equivalent stresses and strains were observed on the metal bars and sternum in the severe type, thereby predicting and confirming the biomechanical characteristics of these types. In conclusion, a novel Nuss procedure simulation for severe types was numerically validated. This underscores the importance of biomechanical evaluation through a novel Nuss procedure simulation when planning actual surgeries for severe types of cases.